2008
DOI: 10.1128/jb.00360-08
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Histone-Like Nucleoid Structuring Protein in the Regulation of rpoS and RpoS-Dependent Genes in Vibrio cholerae

Abstract: Production of the Zn-metalloprotease hemagglutinin (HA)/protease by Vibrio cholerae has been reported to enhance enterotoxicity in rabbit ileal loops and the reactogenicity of live cholera vaccine candidates. Expression of HA/protease requires the alternate sigma factor S (RpoS), encoded by rpoS. The histone-like nucleoid structuring protein (H-NS) has been shown to repress rpoS expression in Escherichia coli. In V. cholerae strains of the classical biotype, H-NS has been reported to silence virulence gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
54
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 67 publications
4
54
0
Order By: Relevance
“…Consistent with this role, H-NS has been shown to silence virulence gene expression in V. cholerae by acting at different levels of the ToxR regulatory cascade, which includes the toxT, tcpA, and ctxA promoters (37). Further, V. cholerae hns mutants have been reported to exhibit diminished motility and intestinal colonization capacity (18,27,49,53). There are numerous evidences indicating that repression by H-NS can be relieved in response to environmental stimuli that activate the expression of other regulators whose binding site overlaps with that of H-NS.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Consistent with this role, H-NS has been shown to silence virulence gene expression in V. cholerae by acting at different levels of the ToxR regulatory cascade, which includes the toxT, tcpA, and ctxA promoters (37). Further, V. cholerae hns mutants have been reported to exhibit diminished motility and intestinal colonization capacity (18,27,49,53). There are numerous evidences indicating that repression by H-NS can be relieved in response to environmental stimuli that activate the expression of other regulators whose binding site overlaps with that of H-NS.…”
mentioning
confidence: 77%
“…Consistently, microarray studies have shown that rpoS mutants express reduced levels of multiple motility and chemotaxis genes, suggesting that rpoS could act at an early stage of the motility regulatory cascade (35). In a previous study, we addressed the role of H-NS in the regulation of V. cholerae RpoS and RpoS-dependent genes that affect motility and HA/protease production (49). We found that H-NS posttranscriptionally affects RpoS expression in a positive manner, which in turn enhances motility and HA/protease production (49).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…V. cholerae rpoS mutants are more sensitive to starvation, high osmolarity, and oxidative stresses, are less motile than their wild-type precursors (Fig. 13), and do not express hapA (Nielsen et al, 2006;Silva et al, 2008;Yildiz & Schoolnik, 1998;Silva & Benitez, 2004). We have recently shown that, similar to HapR, expression of RpoS acts to diminish the c-di-GMP pool .…”
Section: Enhancement Of Motility and Detachment By The General Stressmentioning
confidence: 99%
“…In V. cholerae, hns mutants form small colonies, are incapable of using -glucosides as a carbon source, exhibit diminished motility (Fig. 12) and intestinal colonization capacity, and show altered responses to environmental stresses (Ghosh et al, 2006;Krishnan et al, 2004;Tending et al, 2000;Silva et al 2008). An emerging function of H-NS is the transcriptional silencing of horizontally acquired genes (Lucchini et al, 2006;Navarre et al, 2006;Oshima et al, 2006).…”
Section: The Histone-like Nucleoid Structuring Protein (H-ns) Repressmentioning
confidence: 99%